(untitled) (Jurnal Penelitian Kehutanan Wallacea, 2020)
Earthworms have a role as bioindicators so that their existence is very sensitive to changes in the environment. The decreasing of land quality caused by continuous use (horticultural agriculture) will also decrease the diversity of earthworms. To anticipate degradation of land quality, the land needs to be rested (bero) so that it will facilitate natural recovery. Indicators of land restoration include the diversity and importance index of earthworms. Therefore, the research aim wasto determine the diversity of earthworm in the fallow system lands at KelimutuNational Parkareas. The monolith random sampling method at three soil depths was applied to several fields with different fallow periods (5, 10, 15 and 20 years) to measure importance value index, diversity index, evenness, density, and earthworm biomass. The results showed that there were 4 types of earthworms found in the land given, namely Pontoscolex, Megascolex, Lumbricus and Perithima. Pontoscolex dominates which is indicated by the highest importance value index. While the diversity of earthworms washigher in fallow land with a duration period of 5 and 20 years. The duration of the fallow period is also shown to affect populations of earthworms but has no effect on its biomass. For soil depths not seen no effect at each depth. The results of this study further strengthen the evidence that the application of the bero period can improve land quality by increasing the earthworm population so that land productivity can be maintained.